(3TaGA GdZdjd aj Md ebad Ndjds - (3CHh YHO Gddg eMeO Hf CMeO Hf eMeO Hf ZGRi GdecfGSis; (3Ndjd Hf ESMGb Hf ehSi, VjGA GdOjf GdoLrfpOj GdeGdcj GdeUQj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HfYeI GdESdGe , hLYdfG ef edI fHjfG eMeO CeG HYO , aEf eNJUQ GdTjN GdYdGeI Ndjd ef CaVd JaGSjQ GdCYdGb, hCMdi eG Qeb HGdCMOGb aJMc efi GdYRe GdSGcf dJJHY Jdc GdCeGcf aTQMJgG hSejJg s
(3BNQgG (B:s
(3aEf JZjQ Shb GdSdYI de jcf ddeHJGY QOgG dCf GdbjeI hMHJ hCeG Ef HGYgG Ke QLYJ Edjg HYjH Ch TQGA Ch gHI Ch ejQGK adg GdQO fLR s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdCHhGH hHYV GdcdeGJ hGdahGUd HGdMeQI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdeGdcjs